PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH BRAND IMAGE TERHADAP REPURCHASE INTENTION - Dewi, I G. A. Pt. Riana Pramesti; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 8 No 5 (2019)DO - 10.24843/EJMUNUD.2019.v08.i05.p05, 2019)
The purpose of this study is to provide an explanation of the influence of brand image on consumer satisfaction, the influence of brand image and customer satisfaction on repurchase intention, and the role of consumer satisfaction in mediating the relationship between brand image and repurchase intention. This research was conducted in Denpasar city by distributing questionnaires to the research sample as many as 112 respondents who were selected through purposive sampling technique. The indicators of this study were 16 items which were analyzed using Path analysis, Sobel Test, and VAF Test. The results of this study explain that brand image has a positive effect that is also significant for consumer satisfaction, brand image and also customer satisfaction positively and significantly influence repurchase intention, then consumer satisfaction is able to mediate the relationship between brand image and repurchase intention. The theoretical implication of this study is that brand image can increase consumer satisfaction so as to increase consumer intention to repurchase. The practical implication in this research is that company management must pay more attention to brand image and customer satisfaction because this is a factor that can trigger the emergence of repurchase intention.   Keywords : brand image, customer satisfaction, repurchase intention